(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the healing effects of Moringa oleifera in rats (Rattus norvegicus). Methodology: Moringa leaves were collected, dried, crushed, mixed with hexane solvent and filtered. After removing the solvent and moisture, he combined the resulting concentrate with the natrosol gel, reaching concentrations of 5% and 10%. 60 male rats were divided into 4 groups: negative control (without treatment), positive control (treated with AGE), Moringa 5% (treated with Moringa gel at 5%) and Moringa 10% (treated with Moringa gel at 10 %). It was subdivided into three groups of 5 animals according to the evaluation period (7, 14 and 21 days). A longitudinal incision (3.0 cm) was made in the cervical region; in the dorsal region an area of ​​2 cm² was demarcated and resected with a punch. Result: In the analysis of healing resistance, after 7 days, the 5% and 10% moringa groups showed a significant regression; after 14 and 21 days, the Moringa 10% group showed statistical significance when compared to the other groups. In the microscopic analysis, after 7 days, collagen fibers more evident in the Moringa groups 5% and 10%; after 14 and 21 days, few blood vessels, low intensity inflammatory reaction and more organized and intense collagen deposition in the Moringa 10% group. Conclusion: Moringa, especially at a concentration of 10%, proved to be beneficial in the repair process of surgically induced skin wounds in rats.